Implementation Of Transformation Legitimacy Function Candra Bhairawa Manuscript For The Community - Parta, Ida Bagus Made Wisnu; Suarka, I Nyoman; Cika, I Wayan; Suastika, I Made (e-Journal of Linguistics, 2021)
The people enthusiastically received the Candra Bhairawa manuscript. Its purpose of altering legitimacy is to validate Shiva Buddha syncretism in Bali. Problem in this study is text transformation on Candra Bhairawa manuscript for community. To describe Candra Bhairawa manuscript as one of the texts that justify Shiva Buddhist syncretism in society. This study is qualitative and uses structural functionalism theory. The Candra Bhairawa manuscript data was analyzed using descriptive statistics and reading methods. Data analysis in prose and poetry with Old Javanese and Balinese into a descriptive form in Indonesian. Based on the value systems and beliefs of individuals and groups, the research explains the legitimacy process. The syncretism of Shiva Buddha combines Shiva and Buddha teachings. That the two teachings of Shiva (karma sanyasa) and Buddhist teachings (yoga sanyasa) may be combined into one is proof of the legitimacy of Shiva Buddhist syncretis which can bring balance and harmony.